CO2 Hydrogenation to Methanol: Effects of Reaction Temperatures and Pellet Crushing on the Catalytic Performance - Berahim, N.H. (Springer Science and Business Media B.V., 2021)
Methanol synthesis from CO2 hydrogenation is a potent clean energy solution that can address both climate change and depletion of natural resources. Nevertheless, the development of effective catalyst capable of providing adequate activity and stability remains one of the most significant barriers to the real implementation of such a reaction. In view of this, Cu/ZnO tri-promoted with transition metals from Group IV (GIV), V (GV) and VII (GVII) supported on SBA-15 pellet has been synthesized using the impregnation technique. The synthesized catalyst was characterized using temperature-programmed reduction (TPR), field emission scanning electron microscope (FESEM), N2 adsorption/desorption and X-ray fluorescence (XRF) techniques. The catalytic performance of the catalyst in a CO2 hydrogenation reaction was evaluated using a fixed-bed reactor and the products were determined using online GC. Effects of reaction temperatures and crushing of the pellet were also investigated in this study. The catalyst resulted in highest MeOH selectivity of 54.59 at 250Â Â°C. Crushing the pellet into smaller size did not affect the catalytic performance significantly. Â© 2021, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.